This repository has been archived by the owner on May 18, 2021. It is now read-only.
-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathwk5.tex
519 lines (364 loc) · 20.3 KB
/
wk5.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
%
% This is a borrowed LaTeX template file for lecture notes for CS267,
% Applications of Parallel Computing, UCBerkeley EECS Department.
% Now being used for CMU's 10725 Fall 2012 Optimization course
% taught by Geoff Gordon and Ryan Tibshirani. When preparing
% LaTeX notes for this class, please use this template.
%
% To familiarize yourself with this template, the body contains
% some examples of its use. Look them over. Then you can
% run LaTeX on this file. After you have LaTeXed this file then
% you can look over the result either by printing it out with
% dvips or using xdvi. "pdflatex template.tex" should also work.
%
\documentclass[twoside]{article}
\setlength{\oddsidemargin}{0.25 in}
\setlength{\evensidemargin}{-0.25 in}
\setlength{\topmargin}{-0.6 in}
\setlength{\textwidth}{6.5 in}
\setlength{\textheight}{8.5 in}
\setlength{\headsep}{0.75 in}
\setlength{\parindent}{0 in}
\setlength{\parskip}{0.1 in}
%
% ADD PACKAGES here:
%
\usepackage{amsmath,amsfonts,graphicx,soul}
%
% The following commands set up the lecnum (lecture number)
% counter and make various numbering schemes work relative
% to the lecture number.
%
\newcounter{lecnum}
\renewcommand{\thepage}{\thelecnum-\arabic{page}}
\renewcommand{\thesection}{\thelecnum.\arabic{section}}
\renewcommand{\theequation}{\thelecnum.\arabic{equation}}
\renewcommand{\thefigure}{\thelecnum.\arabic{figure}}
\renewcommand{\thetable}{\thelecnum.\arabic{table}}
\newcommand*\conj[1]{\bar{#1}}
\newcommand*\mean[1]{\bar{#1}}
\newcommand{\indep}{\rotatebox[origin=c]{90}{$\models$}}
%
% The following macro is used to generate the header.
%
\newcommand{\lecture}[4]{
\pagestyle{myheadings}
\thispagestyle{plain}
\newpage
\setcounter{lecnum}{#1}
\setcounter{page}{1}
\noindent
\begin{center}
\framebox{
\vbox{\vspace{2mm}
\hbox to 6.28in { {\bf STAT7017 Big Data Statistics
\hfill Semester 2 2018} }
\vspace{4mm}
\hbox to 6.28in { {\Large \hfill Lecture #1: #2 \hfill} }
\vspace{2mm}
\hbox to 6.28in { {\it Lecturer: #3 \hfill Scribes: #4} }
\vspace{2mm}}
}
\end{center}
\markboth{Lecture #1: #2}{Lecture #1: #2}
{\bf Note}: {\it LaTeX template courtesy of UC Berkeley EECS dept.}
{\bf Disclaimer}: {\it These notes have not been subjected to the
usual scrutiny reserved for formal publications. They may be distributed
outside this class only with the permission of the Instructor.}
\vspace*{4mm}
}
%
% Convention for citations is authors' initials followed by the year.
% For example, to cite a paper by Leighton and Maggs you would type
% \cite{LM89}, and to cite a paper by Strassen you would type \cite{S69}.
% (To avoid bibliography problems, for now we redefine the \cite command.)
% Also commands that create a suitable format for the reference list.
\renewcommand{\cite}[1]{[#1]}
\def\beginrefs{\begin{list}%
{[\arabic{equation}]}{\usecounter{equation}
\setlength{\leftmargin}{2.0truecm}\setlength{\labelsep}{0.4truecm}%
\setlength{\labelwidth}{1.6truecm}}}
\def\endrefs{\end{list}}
\def\bibentry#1{\item[\hbox{[#1]}]}
%Use this command for a figure; it puts a figure in wherever you want it.
%usage: \fig{NUMBER}{SPACE-IN-INCHES}{CAPTION}
\newcommand{\fig}[3]{
\vspace{#2}
\begin{center}
Figure \thelecnum.#1:~#3
\end{center}
}
% Use these for theorems, lemmas, proofs, etc.
\newtheorem{theorem}{Theorem}[lecnum]
\newtheorem{lemma}[theorem]{Lemma}
\newtheorem{proposition}[theorem]{Proposition}
\newtheorem{claim}[theorem]{Claim}
\newtheorem{corollary}[theorem]{Corollary}
\newtheorem{definition}[theorem]{Definition}
\newenvironment{proof}{{\bf Proof:}}{\hfill\rule{2mm}{2mm}}
% **** IF YOU WANT TO DEFINE ADDITIONAL MACROS FOR YOURSELF, PUT THEM HERE:
\newcommand\E{\mathbb{E}}
\begin{document}
%FILL IN THE RIGHT INFO.
%\lecture{**LECTURE-NUMBER**}{**DATE**}{**LECTURER**}{**SCRIBE**}
\lecture{5}{20 August}{Dr Dale Roberts}{Rui Qiu}
%\footnotetext{These notes are partially based on those of Nigel Mansell.}
% **** YOUR NOTES GO HERE:
% Some general latex examples and examples making use of the
% macros follow.
%**** IN GENERAL, BE BRIEF. LONG SCRIBE NOTES, NO MATTER HOW WELL WRITTEN,
%**** ARE NEVER READ BY ANYBODY.
Now that we have some integration tools at our disposal, we can consider some integrals fro moments and statistics of the MP distribution.
\textbf{\underline{Moments of the MP distribution}}
\begin{proposition}
For the standard MP distribution $F_y$ with index $y>0$ and $\sigma^2=1$, if holds for any analytic function $f$ on a domain containing interval $[a,b]=[(1\pm \sqrt{y})^2]$,
$$\int f(x)dF_y(x)=-\frac{1}{4\pi i}\oint_{\lvert z\rvert =1}\frac{f(\lvert 1+\sqrt{y}z\rvert ^2)(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{y})}dz.$$
\end{proposition}
\begin{proof}
(We will prove a stronger case later.)
\end{proof}
Let's look at some applications.\\
\underline{Example 1:} Logarithms of eigenvalues are often used in multivariate analysis. Set
$$f(x)=\log(x).$$
Assume $0<y<1$ so that we don't get zero eigenvalues.
\begin{equation}
\begin{split}
\int\log(x)dF_y(x)&=-\frac{1}{4\pi i}\oint_{\lvert z\rvert =1}\frac{\log(\lvert 1+\sqrt{y}z\rvert^2)(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{y})}dz\\
&=-\frac{1}{4\pi i}\oint_{\lvert z\rvert =1}\frac{\log(1+\sqrt{y}z)(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{y}z)}dz-\frac{1}{4\pi i}\oint_{\lvert z\rvert=1}\frac{\log(1+\sqrt{y}\mean{z})(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{z})}dz\\
&= I_1+I_2
\end{split}
\end{equation}
Note $z\in\mathbb{C}$:
\begin{equation}
\begin{split}
\lvert 1+\sqrt{y}z\rvert^2&=(1+\sqrt{y}z)\overline{(1+\sqrt{y}z)}\\
&=(1+\sqrt{y}z)(1+\sqrt{y}\mean{z})
\end{split}
\end{equation}
Q: When do these integrals have singularities?
There is one at the point $z=0$, due to the $\frac{1}{z^2}$ term (``order 2 pole").
Another at $z=-\sqrt{y}$.
Both within contour $\lvert z\rvert=1$.\\
By Cauchy residue theorem,
$$\int_C f(z)dz=2\pi i\sum_{a\in C}Res(f;a)$$
where $a$ are points of singularity.
We need to find the residues at the points $z=0$ and $z=-\sqrt{y}$. We could expand and find the Laurent series but there is an easier way.
\begin{proposition}
If $f$ has a pole of order $n\geq 1$ at $a$. Define $g(z)=(z-a)^nf(z)$ then
$$Res(f; a)=\frac{1}{(n-1)!}\lim_{z\to a}g^{(n-1)}(z).$$
\end{proposition}
\begin{proof}
Remember that the residue is the term $c_{-1}$ in the Laurent series expansion of $f(z)$:
$$f(z)=\frac{c_{-n}}{(z-a)^n}+\cdots +\frac{c_{-1}}{z-a}+a_0+\cdots$$
so $g(z)=c_{-n}+\cdots +c_{-1}(z-a)^{n-1}+c_0(z-a)^n+\cdots$ and $g^{(n-1)}(z)=(n-1)!c_{-1}+n(n-1)\cdots2\cdot c_0(z-a)+\cdots$
Hence, $\lim_{z\to a}g^{(n-1)}(z)=g^{(n-1)}(a)=(n-1)!c_{-1}.$
\end{proof}
Applying this proposition at $a=-\sqrt{y}$:
$$\lim_{z\to-\sqrt{y}}\frac{\log(1+\sqrt{y}z)(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{y})}(z-(-\sqrt{y}))=\frac{\log(1-y)(1-y)^2}{y(1-y)}=\log(1-y)\frac{(1-y)}{y}.$$
The singularity at $a=0$ is of order 2, so
$$g(z)=z^2\frac{\log(1+\sqrt{y}z)(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{y})}=\frac{\log(1+\sqrt{y}z)(1-z^2)^2}{(1+\sqrt{y}z)(z+\sqrt{y})}$$
$$g'(z)=\frac{\sqrt{y}(1-z^2)^2}{(\sqrt{y}+z)(1+\sqrt{y}z)^2}-\frac{4z(1-z^2)\log(1+\sqrt{y}z)}{(\sqrt{y}+z)(1+\sqrt{y}z)}-\frac{\sqrt{y}(1-z^2)^2\log(1+\sqrt{y}z)}{(\sqrt{y}+z)(1+\sqrt{y}z)^2}-\frac{(1-z^2)^2\log(1+\sqrt{y}z)}{(\sqrt{y}+z)^2(1+\sqrt{y}z)}$$
$$g'(0)=\frac{\sqrt{y}}{\sqrt{y}}-0-0-0=1.$$
So by the residue theorem
\begin{equation}
\begin{split}
I_1&=-\frac{1}{4\pi i}\left[2\pi\cdot\left(\log(1-y)\frac{(1-y)}{y}+1\right)\right]\\
&=-\frac{1}{2}\left(\log(1-y)\frac{(1-y)}{y}+1\right)
\end{split}
\end{equation}
Now for $I_2$ we have
$$I_2=-\frac{1}{4\pi i}\oint_{\lvert z\rvert =1}\frac{\log(1+\sqrt{y}\mean{z})(1-z^2)^2}{z^2(1+\sqrt{y}z)(z+\sqrt{y})}dz.$$
We shall make the change of variable $s=\mean{z}$ and notice that since $\lvert z\rvert =1$, we have
$$\frac{1}{z}=\frac{1}{e^{i\theta}}=e^{-i\theta}=\mean{z}$$
So
$$I_2=-\frac{1}{4\pi i} \oint_{\lvert s\rvert=1}\frac{\log(1+\sqrt{y}s)\left(1-\left(\frac1s\right)^2\right)^2}{\left(\frac1s\right)^2(1+\sqrt{y}\left(\frac1s\right))(\frac1s+\sqrt{y})}(-\frac{1}{s^2})ds.$$
and this can be shown to be
$$I_2=I_1.$$
hence, $I=-\log(1-y)\frac{(1-y)}{y}-1.$
\underline{Example 2:} We can calculate the \underline{mean} of the MP distribution. For all $y>0$,
$$\int xdF_y(x)=1.$$
\begin{proof}
This can be shown in the same way as Example 1.
\end{proof}
For any monomial function $f(x)=x^k$ for $k\in\mathbb{N}$, the residue approach becomes tedious. There is a direct proof as well. (Bai \& Silverstein 2010; Lemma 3.1).\\
\begin{proposition}
The moments of the standard MP distribution
$$\beta_k:=\int x^kdF_y(x)=\sum^{k-1}_{r=0}\frac{1}{r+1}{k\choose r}{k-1 \choose r}y^r$$
\end{proposition}
\begin{proof}
$$P_y(x)=\begin{cases}
\frac{1}{2\pi xy}\sqrt{(b-x)(x-a)}, a\leq x\leq b\\
0,\ \text{otherwise.}
\end{cases}$$
$a=(1-\sqrt{y})^2, b=(1+\sqrt{y})^2$.
$$\beta_k=\frac{1}{2\pi y}\int^b_a x^{k-1}\sqrt{(b-x)(x-a)}dx.$$
Set $x= 1+y+z, dx=dz, x=a\implies (1-\sqrt{y})^2=1+y+z, z=(1-\sqrt{y})^2-1-y=-2\sqrt{y}$.
$(b-x)(x-a)=(2\sqrt{y}-z)(2\sqrt{y}+z)=(4y-z^2), x=b\implies z=2\sqrt{y}.$
So
$$\beta_k=\frac{1}{2\pi y}\int^{2\sqrt{y}}_{-2\sqrt{y}}(1+y+z)^{k-1}\sqrt{4y-z^2}dz.$$
Recall $(a+b)^\alpha=\sum^\alpha_{k=0}{\alpha\choose k}a^kb^{\alpha-k}, {\alpha\choose k}:=\frac{\alpha!}{k!(\alpha-k)!}$
So here $a=1+y, b=z, \alpha=k-1.$
\begin{equation}
\begin{split}
\beta_k&=\frac{1}{2\pi y}\int^{2\sqrt{y}}_{-2\sqrt{y}}\sum{k-1}_{l=0}{k-1\choose l}(1+y)^{k-1-l}z^{l}\sqrt{4y-z^2}dz\\
&=\frac{1}{2\pi y}\sum^{k-1}_{l=0}{k-1\choose l}(1+y)^{k-1-l}\int^{2\sqrt{y}}_{-2\sqrt{y}}z^l\sqrt{4y-z^2}dz.
\end{split}
\end{equation}
We continue to set $z=2\sqrt{y}u, dz=2\sqrt{y}du\implies 4y-z^2=1-u^2.$
$z=-2\sqrt{y}\implies u=-1; z=2\sqrt{y}\implies u=1.$
\begin{equation}
\begin{split}
\beta_k&=\frac{1}{2\pi y}\sum^{k-1}_{l=0}{k-1\choose l}(1+y)^{k-1-l}2\sqrt{y}(2\sqrt{y})^l\int^1_{-1}u^l\sqrt{1-u^2}du\\
&=\frac{1}{2\pi y}\sum^{k-1}_{l=0}{k-1\choose l}(1+y)^{k-1-l}(4y)^{\frac{l+1}{2}}\int^1_{-1}u^l\sqrt{1-u^2}du\\
&=\frac{1}{2\pi y}\sum^{\frac{k-1}{2}}_{l=0}{k-1\choose 2l}(1+y)^{k-1-2l}(4y)^{l+1}\int^1_{-1}u^{2l}\sqrt{1-u^2}du
\end{split}
\end{equation}
Set $u=\sqrt{w}, du=\frac{1}{2}\frac{1}{\sqrt{w}}dw, u=-1, w=1.$
\begin{equation}
\begin{split}
\beta_k&=\frac{1}{2\pi u}\sum^{\frac{k-1}{2}}_{l=0}{k-1\choose 2l}(1+y)^{k-1-2l}(4y)^{l+4}\int^1_0w^{l-\frac{1}{2}}\sqrt{1-w}dw.
\end{split}
\end{equation}
As $\Gamma(t):=\int^\infty_{0}x^{t-1}e^{-x}dx, \Gamma(n):=(n-1)!, \Gamma(l+\frac{1}{2})=\frac{(2l)!}{4^l l!}\sqrt{\pi}.$
As $\int^1_0w^{l-\frac{1}{2}}\sqrt{1-w}dw=\frac{\sqrt{\pi}\Gamma(l+\frac12)}{2\Gamma(2+l)}$ if $l>\frac{1}{2}$. We continue:
\begin{equation}
\begin{split}
\beta_k &=\sum^{[(k-1)/2]}_{l=0}\frac{1}{2\pi y}\frac{(k-1)!}{(2l)!((k-1)-2l)!}\frac{\sqrt{\pi}}{2}\frac{(2l)!\sqrt{\pi}}{4^l l!(l+1)!}4^{l+1}y^{l+1}(1+y)^{k-1-2l}\\
&=\sum^{[(k-1)/2]}_{l=0}\frac{(k-1)!}{l!(l+1)!(k-1-2l)!}y^l(1+y)^{k-1-2l}
\end{split}
\end{equation}
As $(1+y)^{k-1-2l}=\sum^{k-1-2l}_{s=0}{k-1-2l\choose s}y^s=\sum^{k-1-2l}_{s=0}\frac{(k-1-2l)!}{s!(k-1-2l-s)!}y^s$, continue:
\begin{equation}
\begin{split}
\beta_k&=\sum^{[(k-1)/2]}_{l=0}\frac{(k-1)!}{l!(l+1)!(k-1-2l)!}y^l\sum^{k-1-2l}_{s=0}\frac{(k-1-2l)!}{s!(k-1-2l-s)!}y^s\\
&=\sum^{[(k-1)/2]}_{l=0}\sum^{k-1-2l}_{s=0}\frac{(k-1)!}{l!(l+1)!s!(k-1-2l-s)!}y^{l+s}
\end{split}
\end{equation}
Substitute $r=l+s, s=0\implies r=l, s=k-1-2l\implies r=k-1-l$. Continue:
\begin{equation}
\begin{split}
\beta_k&=\sum^{[(k-1)/2]}_{l=0}\sum^{k-1-l}_{r=l}\frac{(k-1)!}{l!(l+1)!s!(k-1-r-l)!}y^r\\
&=\frac{1}{k}\sum^{k-1}_{r=0}{k\choose r}y^r\sum^{\min(r,k-1-r)}_{l=0}{r\choose l}{k-r \choose k-r-l-1}\\
&=\frac{1}{k}\sum^{k-1}_{r=0}{k\choose r}{k\choose r+1}y^r=\sum^{k-1}_{r=0}\frac{1}{r+1}{k\choose r}{k-1\choose r}y^r.
\end{split}
\end{equation}
\end{proof}
\underline{\textbf{Fubini theorem for sequences:}} If $\sum^\infty_{n=0}\sum^\infty_{m=0}\lvert a_{nm}\rvert < \infty$ then
$$\sum^{\infty}_{m=0}\sum^{\infty}_{n=0}a_{mn}=\sum^{\infty}_{n=0}\sum^{\infty}_{m=0}a_{mn}.$$
\underline{How did I use that?}
\begin{equation}
\begin{split}
\sum^{[(k-1)/2]}_{l=0}\sum^{k-1-l}_{r=l}\frac{(k-1)!}{l!(l+1)!(r-l)!(k-1-r-l)!}y^r&=\sum^\infty_{l=0}\mathbf{1}_{(l\leq [(k-1)/2])}\sum^\infty_{r=0}\mathbf{1}_{(r\geq l)}\mathbf{1}_{(r\leq k-1-l)}\\
&=\sum^\infty_{l=0}\sum^{\infty}_{r=0}\mathbf{1}_{(l\leq [(k-1)/2])}\mathbf{1}_{(l\leq r)}\mathbf{1}_{(l\leq k-1-r)}\mathbf{1}_{(r\leq k-1)}\\
&=\sum^{k-1}_{r=0}\sum^{\min(r,k-1-r)}_{l=0}\square\\
\square&=\frac{k!}{r!(k-r)!}y^r\frac{(k-1)!r!(k-r)!}{k!l!(l+1)!(r-l)!(k-1-r-l)!}\\
&={k\choose r}y^r\frac{1}{k}\cdot \frac{r!}{l!(r-l)!}\cdot \frac{(k-r)!}{(l+1)!(k-1-r-l)!}\\
&\text{note:}\ k-r-(k-1-r-l)=l+1\\
&=\frac{1}{k}{k\choose r}y^r{r\choose l}{k-r \choose k-1-r-l}
\end{split}
\end{equation}
So we plug $\square$ back in to have
$$=\sum^{k-1}_{r=0}\frac{1}{k}{k\choose r}y^r\sum^{\min(r,k-1-r)}_{l=0}{r\choose l}{k-r\choose k-1-r-l}.$$\\
\underline{\textbf{Generalized MP distribution}}
Previously, we've seen the case where the population covariance matrix has the simple form $\sum=\sigma^2\mathbf{I}_p$.
We can consider a slightly more general case if we make the assumption that the observation vectors $\{y_k\}_{1\leq k\leq n}$ can be represented as
$$y_k:=\sum^{1/2}x_k, x_k\text{ iid}, \sum\text{ nonnegative square root of }\sum.$$
This gives the associated covariance matrix
\begin{equation}
\begin{split}
\tilde{\mathbf{B}}_n&=\frac{1}{n}\sum^n_{k=1}\mathbf{y}_k\mathbf{y}_k^*=\sum^{1/2}\left(\frac1n\sum^n_{k=1}\mathbf{x}_k\mathbf{x}_k^*\right)\sum^{1/2}\\
&=\sum^{1/2}\mathbf{S}_n\sum^{1/2}
\end{split}
\end{equation}
$S_n$ is the sample covariance matrix with iid components.
The eigenvalues of $\tilde{B}_n$ are the same as $\mathbf{S}_n\sum$.
The following result holds for $\mathbf{B}_n=\mathbf{S}_n\mathbf{T}_n$ for general nonnegative definite matrix $\mathbf{T}_n$. ($\mathbf{T}_n=\sum$ is a special case.)
\begin{theorem}
Let $\mathbf{S}_n$ be the sample covariance matrix $\mathbf{S}_n=\frac1n\sum^n_{i=1}\mathbf{x}_i\mathbf{x}^*$ with iid components and let $(\mathbf{T}_n)$ be a sequence of nonnegative definite Hermitian matrices of size $p\times p$.
Define $\mathbf{B}_n=\mathbf{S}_n\mathbf{T}_n$ and assume:
\begin{enumerate}
\item The entries $(x_{jk})$ of the data matrix $\mathbf{X}=(\mathbf{x}_1,\dots, \mathbf{x}_n)$ are iid with mean zero and variance $\mathbf{1}$.
\item The data dimension to sample size ratio $p/n\to y>0$ as $n\to \infty$.
\item The sequence $(\mathbf{T}_n)$ is either deterministic or independent of $(\mathbf{S}_n)$.
\item Almost surely, the sequence $(H_n=F^{\mathbf{T}_n})$ of the ESD of $(\mathbf{T}_n)$ weakly converges to a non-random probability measure $H$.
\end{enumerate}
Then, almost surely, $F$ (???) weakly converges to a non-random probability measure $F_{y,H}$. Its Stieltjes transform is given by
\begin{equation}S(z)=\int\frac{1}{t(1-y-yzs(z))-z}dH(t), z\in\mathbb{C}^+\end{equation}
Notice that the ST of $F_{y,H}$ is \underline{implicitly} defined. It can be shown that a unique solution exists, but, unfortunately, no closed-form solution exists. (see Silverstein \& Combettes 1992)
\end{theorem}
There is a better way to represent the ST of $F_{y,H}$. Consider for $\mathbf{B}_n$ a \underline{companion matrix}.
$$\underline{\mathbf{B}_n}=\frac{1}{n}\mathbf{X}^*\mathbf{TX}\ \ \ \ \ \ \ \ \ \ \text{ size }n\times n$$
Both matrices share the same nonzero eigenvalues so their ESD satisfy
$$nF(???)-pF^{\mathbf{B}_n}=(n-p)\mathbf{S}_0(???).$$
\underline{Note:} Given two matrices $\mathbf{A}_{p\times q}$ and $\mathbf{B}_{q\times p}$ where $p\geq q$, eigenvalues of $\mathbf{AB}$ is that of $\mathbf{BA}$ augmented by $p-q$ zeros.
$$\mathbf{B}_n=\mathbf{S}_n\mathbf{T}_n=\frac{1}{n}\mathbf{XX}^*\mathbf{T}_n, \underline{\mathbf{B}_n}=\frac{1}{n}\mathbf{X^*TX},\text{ where $\mathbf{X}$ is a $p\times n$ matrix.}$$
When $p/n\to y>0, F^{\mathbf{B}_n}$ has limit $F_{c,H}$ if and only if $F^{\underline{\mathbf{B}_n}}$ has limit $\underline{F}_{c,H}$. In this case, the limit satisfies
$$\underline{F}_{c,H}-yF_{c,H}=(1-y)S_0(???).$$
and their ST are related by
$$\underline{s}(z)=-\frac{1-y}z+ys(z).$$
Now substituting $\underline{s}$ for s in (5.12) yields
$$\underline{s}(z)=\left(z-y\int\frac{t}{1+ts(z)}dH(t)\right)^{-1}$$
Solving in $z$ gives:
\begin{equation}z=-\frac{1}{\underline{s}(z)}+y\int\frac{t}{1+t\underline{s}(z)}dH(t)\end{equation}
which defines the inverse function of $\underline{s}$.
\begin{itemize}
\item (5.12) is called the \underline{Marchenko-Pastur equation} and\\
\item (5.13) is the \underline{Silverstein equation}.
\end{itemize}
\underline{\textbf{Limiting spectral distribution for Random Fisher matricecs}}
In the univariate case, when we need to test equality between the variances of 2 Gaussian populations, a Fisher statistic of the form $S_1^2/S_2^2$ is used where $S_i^2$ are estimators of the unknown variances in the two populations.
The equivalent for the multivariate setting is:
Take two independent samples $\{\mathbf{x}_1,\mathbf{x}_2,\dots,\mathbf{x}_n\}$ and $\{\mathbf{y}_1,\mathbf{y}_2,\dots,\mathbf{y}_n\}$ both from $p$-dimensional population with iid components and finite second moment.
$$\mathbf{S}_1=\frac{1}{n_1}\sum^{n_1}_{k=1}\mathbf{x}_k\mathbf{x}_k^*$$
$$\mathbf{S}_2=\frac{1}{n_2}\sum^{n_2}_{k=1}\mathbf{y}_k\mathbf{y}_k^*$$
Then $\mathbf{F}_n:=\mathbf{S}_1\mathbf{S}_2^{-1}$ is called a Fisher matrix, $\mathbf{n}=(n_1,n_2).$
(Note: need $p\leq n_2$ so that $\mathbf{S}_2$ invertible.)
Let $s>0$ and $0<t<1$. The \underline{Fisher LSD} $F_{s,t}$ is the distribution with density function
$$P_{s.t}(x)=\frac{1-t}{2\pi x(s+tx)}\sqrt{(b-x)(x-a)}, a\leq x\leq b$$
with $a=a(s,t)=\frac{(1-h)^2}{(1-t)^2}, b= b(s,t)=\frac{(1+h)^2}{(1-t)^2}, h=h(s,t)=(s+t-st)^{1/2}$.
When $s>1, F_{s,t}$ has a mass at $x=0$ of value $1-\frac{1}{s}$ with the total mass of the rest of the distribution for $x>0$ is equal to $1/s$.
The Fisher LSD has many similarities to the standard MP distribution. This is not a coincidence as the MP LSD $F_y$ is the Fisher LSD $F_{y,0}$ (i.e. $s,y=y,0$)
Also note $t\to 1, a(s,t)\to \frac{1}{2}(1-s)^2, b(s,t)\to \infty$ ($Supp(F_{s,t})$ becomes unbounded).
\begin{theorem}
For an analytic function $f$ on a domain containing $[a,b]$ (as above). We have
$$\int^b_af(x)dF_{s,t}(x)=-\frac{h^2(1-t)}{4\pi i}\oint_{\lvert z\rvert = 1}\frac{f\left(\frac{|1+hz|^2}{(1-t)^2}\right)(1-z^2)^2dz}{z(1+hz)(z+h)(tz+h)(t+hz)}$$
\end{theorem}
\begin{proof}
Using the density $P_{s,t}(x)$.
$$I=\int^b_af(x)dF_{s,t}(x)=\int^b_a f(x)\frac{1-t}{2\pi x(s+xt)}\sqrt{(x-a)(b-x)}dx$$
Make change of variable $x=\frac{1+h^2+2h\cos\theta}{(1-t)^2},\theta\in(0,\pi)$.
\begin{equation}
\begin{split}
x-a &=\frac{1+h^2+2h\cos\theta}{(1-t)^2}-\frac{(1-h)^2}{(1-t)^2}=\frac{2h+2h\cos\theta}{(1-t)^2}\\
b-x&=\frac{(1+h)^2}{(1-t)^2}-\frac{1+h^2+2h\cos\theta}{(1-t)^2}=\frac{2h-2h\cos\theta}{(1-t)^2}\\
\sqrt{(x-a)(b-x)}&=\sqrt{\frac{(2h)^2}{(1-t)^4}(1-\cos\theta)(1+\cos\theta)}\\
&=\frac{2h}{(1-t)^2}\sin\theta\\
x&=a \implies \cos\theta = \frac{a(1-t)^2-(1+h^2)}{2h}=0\implies \theta =0\\
x&=b\implies \theta =\pi \\
dx&=\frac{-2h\sin\theta}{(1-t)^2}d\theta
\end{split}
\end{equation}
Hence
\begin{equation}
\begin{split}
I&=\frac{2h^2(1-t)}{\pi}\int^{\pi}_{0}\frac{f\left(\frac{1+h^2+2h\cos\theta}{(1-t)^2}\right)\sin^2\theta d\theta}{(1+h^2+2h\cos\theta)(s(1-t)^2+t(1+h^2+2h\cos\theta))}\\
&=\frac{h^2(1-t)}{\pi}\int^{2\pi}_0\frac{f\left(\frac{1+h^2+2h\cos\theta}{(1-t)^2}\right)\sin^2\theta d\theta}{(1+h^2+2h\cos\theta )(s(1-t)^2+t(1+h^2+2h\cos\theta))}
\end{split}
\end{equation}
Now let $z=e^{i\theta}$,
\begin{equation}
\begin{split}
1+h^2+2h\cos\theta &= \lvert 1+hz\rvert^2\\
\sin\theta &=\frac{z-z^{-1}}{2i}\\
\log(z)=i\theta &\implies \theta =\frac{1}{i}\log(z)\implies d\theta =\frac{1}{iz}dz.\\
I&=-\frac{h^2(1-t)}{4\pi i}\oint_{|z|=1}\frac{f\left(\frac{|1+hz|^2}{(1-t)^2}\right)(1-z^2)^2dz}{z^3|1+hz|^2(s(1-t)^2+t|1+hz|^2)}
\end{split}
\end{equation}
On $|z|=1$, we have $|1+hz|^2=(1+hz)(1+hz^{-1})$.
So expanding denominator and simplifying we have the result.
\end{proof}
\underline{Example:} Take $(s,t)=(y,0)$ and we get the result for MP distribution.
\underline{Example 2:} The first two moments are
$$\int xdF_{s,t}(x)=\frac{1}{1-t}, \int x^2dF_{s,t}(x)=\frac{h^2+1-t}{(1-t)^3}.$$
Hence the variance equals $\frac{h^2}{(1-t)^3}$.
\end{document}